Penerapan Pembelajaran Matematika Kontekstual Terkait Kesehatan untuk Meningkatkan Pemahaman Siswa di Sekolah Dasar - Andri Imam Subekhi; Teguh Ardianto; Swastika Oktavia (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2022)
This Classroom Action Research (CAR) aims to improve elementary school students' understanding in mathematics learning through the application of a contextual approach associated with health topics. The focus of the research is to see how the use of health problems in mathematics problems can motivate students to better understand mathematical concepts such as measurement, statistics, and basic arithmetic. This research was conducted in two cycles, with each cycle involving the planning, action, observation, and reflection stages. The results of the study indicate that the use of a health context in mathematics learning can increase students' active participation and their understanding of the material being taught.